1996
DOI: 10.1046/j.1365-2141.1996.d01-1755.x
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi's anaemia presenting as acute myeloid leukaemia in adulthood

Abstract: We describe a 28-year-old male patient who presented with apparently de novo acute myeloid leukaemia (AML) who was subsequently found to have Fanconi's anaemia (FA). The gene for complementation group A (FAA) has recently been localized to chromosome 16q24.3 and utilizing genetic markers closely linked to this locus we were able to conclude that this patient was likely to belong to complementation group A. FA presenting as AML is an exceptionally rare event and all previously described cases have occurred in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…A recent retrospective study of 145 FA cases showed that certain congenital abnormalities were potential risk indicators for the development of bone marrow failure; FA patients with abnormal radii had a 5·5 times increased risk of developing bone marrow failure compared with those cases with normal radii and the risk also increased with the number of heart, kidney, head, hearing and developmental abnormalities present (Rosenberg et al , 2004). In those children without congenital abnormalities the development of haematological abnormalities can be the first presenting feature of FA and can occasionally be the presenting feature in adulthood (Liu et al , 1991; Cavenagh et al , 1996).…”
Section: Fa – Haematological Aspectsmentioning
confidence: 99%
“…A recent retrospective study of 145 FA cases showed that certain congenital abnormalities were potential risk indicators for the development of bone marrow failure; FA patients with abnormal radii had a 5·5 times increased risk of developing bone marrow failure compared with those cases with normal radii and the risk also increased with the number of heart, kidney, head, hearing and developmental abnormalities present (Rosenberg et al , 2004). In those children without congenital abnormalities the development of haematological abnormalities can be the first presenting feature of FA and can occasionally be the presenting feature in adulthood (Liu et al , 1991; Cavenagh et al , 1996).…”
Section: Fa – Haematological Aspectsmentioning
confidence: 99%
“…67 Furthermore, no case presenting initially as MDS or AML without bone marrow failure (BMF) has been reported in a patient older than 28 years. 68 Xie et al 69 suggested, based on observations from coimmunoprecipitation studies, that AML cells from non-FA patients may exhibit abnormal FA protein complex formation, but the functional significance of the observations was unclear. Specifically, MMC sensitivity was not reported in all cells tested, FA genes were not sequenced, complementation studies were not performed, FANCD2-S/L status was not examined (the identification of FANCD2 was reported after the publication of the report by Xie et al 69 ), and nonleukemic cells from the patients with AML were not analyzed.…”
Section: Genetic Analysis Of a Lymphoblastoid Cell Line From The Samementioning
confidence: 99%
“…5,32,34 Posteriormente, un paciente adulto joven con anemia de Fanconi, aún sin falla medular evidente, puede diagnosticarse debido a infertilidad o cáncer, específicamente carcinoma de células escamosas de cabeza y cuello, síndrome mielodisplásico o leucemia mieloide aguda. 19,[35][36][37][38][39] La importancia del diagnóstico temprano en el paciente con anemia de Fanconi y su familia son: a) Finalización de la odisea diagnóstica. b) Búsqueda, prevención y manejo de comorbilidades asociadas (alteraciones del desarrollo, hematológicas y oncológicas).…”
Section: Sospecha De Anemia De Fanconi Antes De Las Alteraciones Hema...unclassified